Synthesis and Characterization of the Copper(II) Complex of a Nucleic Acid Constituent, Adenosine - K. Mukherjea, Kalyan; Sarkar, S. (Asian Journal of Chemistry, 2016)
Copper(II)-adenosine complex has been synthesized in aqueous medium (pH 6) and characterized by elemental analysis, infrared, 1H NMR electronic spectral and magnetic moment data and ESR study. From IR spectral analysis it is concluded that the C6–NH2 group and N7 nitrogen of adenosine is involved in coordination with Cu(II) ion. This is most probable as it leads to formation of stable five-membered chelate ring. The formation of Cu–Cl bond is also evident from elemental analysis and the IR spectral data. The binding mode has also been confirmed from 1H NMR studies. From electronic spectral analysis, it is proposed that the Cu(II)-adenosine complex assumes predominantly a square-planar geometry. This is also supported by magnetic moment measurements and EPR studies.